Improved disturbance rejection for predictor-based control of MIMO linear systems with input delay. Issue 3 (17th February 2018) - Shi, Shang; Liu, Wenhui; Lu, Junwei; Chu, Yuming
ABSTRACT: In this paper, we are concerned with the predictor-based control of multi-input multi-output (MIMO) linear systems with input delay and disturbances. By taking the future values of disturbances into consideration, a new improved predictive scheme is proposed. Compared with the existing predictive schemes, our proposed predictive scheme can achieve a finite-time exact state prediction for some smooth disturbances including the constant disturbances, and a better disturbance attenuation can also be achieved for a large class of other time-varying disturbances. The attenuation of mismatched disturbances for second-order linear systems with input delay is also investigated by using our proposed predictor-based controller.